Assessment of the Utility of Multiparametric Magnetic Resonance Imaging for Initial Detection of Prostate Cancer - Doykov, Mladen; Chervenkov, Lyubomir; Tsvetkova-Trichkova, Silvia; Doykova, Katya; Georgiev, Aleksandar (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: An accurate diagnosis is essential for the effective treatment of prostate cancer (PCa) and for the patients’ well-being. AIM: Thе main purpose of this study was to assess the utility of multiparametric magnetic resonance imaging (mp-MRI) for initial detection of PCa among the Bulgarian population of men with prostate diseases. MATERIALS AND METHODS: Fifty-three patients, aged 44 to 82 years, were evaluated for clinically significant PCa. Assessment methods included prostate-specific antigen (PSA) serum levels, transrectal ultrasonography (TRUS), GE Discovery 3T MRI, and 12-core TRUS biopsy. RESULTS: mp-MRI showed 83.20% concordance with TRUS biopsy: sensitivity of 91.43% (76.90–98.20), specificity of 75.00% (34.90–96.80), positive predictive values 94.10% (82.80–98.20) and negative predictive values 66.70% (38.70–86.40). Of the patients classified in prostate imaging–reporting and data system (PI-RADS) levels 4 and 5, 94.12% had positive TRUS biopsy, as well as 44.40% of PI-RADS had level 3. Irrespective of the patients’ age and PSA, PI-RADS was found to be a significant predictor of a positive TRUS biopsy (p = 0.009). PSA serum levels showed a low concordance with TRUS biopsy (area under the curve = 0.539; 95% confidence interval [CI]: 0.363–0.712) and a low, although significant, correlation with PI-RADS (rs = 0.416; 95% CI: 0.164–0.617). CONCLUSION: According to our findings, mp-MRI and TRUS biopsy have a high level of concordance for the initial detection of PCa. The incorporation of mp-MRI into the diagnostic pathway for PCa can significantly reduce the number of incorrect diagnoses based on PSA serum levels and/or suspicious physical and digital examinations.